(untitled) (Biological Sciences - PJSIR, 2002)
The objective of this study is to note the results of modified Atmosphere Packaging (MAP) Technology for post harvest preservation of carrots (Daucus carrota L.). It was observed that peeling treatment, film type and days of storage had a significant effect on CO, and 0 percentages within bags of carrots stored at 7°C. The bags with peeled carrots contained significantly less CO , 9.4% and more 0 , 16. 1% than non-peeled carrots, 17.6% CO and 14.3% 0 durin g the 28 day 2 2 2 2 storage period